Combinative aspects of leadership style and emotional intelligence. Issue 1 (7th March 2016) - Li, Zhidong; Gupta, Bindu; Loon, Mark; Casimir, Gian
Abstract : Purpose: – The purpose of this paper is to examine whether the leader's emotional intelligence influences the leader's preferences for different ways of combining leadership behaviors (i.e. combinative aspects of leadership style). Design/methodology/approach: – The authors used a hybrid design to collect the data to avoid common-method biases. The authors described a high-stress workplace in a vignette and asked participants to rank four styles of combining a task-oriented leadership (i.e. Pressure) statement and a socio-emotional leadership (i.e. Support) statement. The authors then asked participants to complete a Likert-scale based questionnaire on emotional intelligence. Findings: – The authors found that leaders who prefer to provide Support immediately before Pressure have higher levels of emotional intelligence than do leaders who prefer the three other combinative styles. Leaders who prefer to provide Pressure and Support separately (i.e. provide Pressure 30 minutes after Support) have the lowest levels of emotional intelligence. Research limitations/implications: – A key implicit assumption in the work is that leaders do not want to evoke negative emotions in followers. The authors did not take into account factors that influence leadership style which participating managers would be likely to encounter on a daily basis such as the relationship with the follower, the follower's level of performance and work experience, the gender of the leader and the gender of the follower, the hierarchical levels of the leader and follower, and the followers' preferred combinative style. The nature of the sample and the use of a hypothetical scenario are other limitations of the study. Practical implications: – Providing leadership behaviors that are regarded as effective is necessary but not enough because the emotional impact of leadership behaviors appears to also depend on how the behaviors are configured. Originality/value: – This is the first study to show that the emotional intelligence of leaders is related to their preferences for the manner in which they combine task and social leadership statements. Furthermore, two-factor theories of leadership propose that the effects of task and social leadership are additive. However, the findings show that the effects are interactive.